2018
DOI: 10.1175/jcli-d-17-0683.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Robustness of Future Extreme Precipitation Intensification in the CMIP5 Ensemble

Abstract: A warming climate is expected to intensify extreme precipitation, and climate models project a general intensification of annual extreme precipitation in most regions of the globe throughout the twenty-first century. We investigate the robustness of this future intensification over land across different models, regions, and seasons and evaluate the role of model interdependencies in the CMIP5 ensemble. Strong similarities in extreme precipitation changes are found between models that share atmospheric physics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 71 publications
5
39
0
Order By: Relevance
“…S8a,c). Earlier studies have also found a larger spread of extreme precipitation changes in dry regions compared wet regions 14,37 . The increasing total uncertainty with decreasing water availability is attributed to the increasing trend of both its components (GCM and hazard quantification method); however, the GCM uncertainty has a much larger contribution in all regions.…”
Section: Resultsmentioning
confidence: 74%
“…S8a,c). Earlier studies have also found a larger spread of extreme precipitation changes in dry regions compared wet regions 14,37 . The increasing total uncertainty with decreasing water availability is attributed to the increasing trend of both its components (GCM and hazard quantification method); however, the GCM uncertainty has a much larger contribution in all regions.…”
Section: Resultsmentioning
confidence: 74%
“…associated with extreme precipitation in low-and high-resolution models in order to gain a better understanding of why higher resolutions generally lead to more intense, and sometimes less realistic, precipitation extremes. Meanwhile, given the widely different skills of climate models in capturing extreme precipitation, our study illustrates how a careful model selection might be necessary when dealing with precipitation extremes and their response to global warming that is largely uncertain over most regions of the globe (Bador et al, 2018;Collins et al, 2013;IPCC, 2013;.…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 98%
“…The spatial patterns of change, however, are heterogeneous across datasets, and precipitation changes at local and regional scales remain uncertain (Fischer et al 2013, Pfahl et al 2017. Increasing intensity of heavy precipitation extremes has been documented, robust across observations and global climate models, when aggregating over the wet and dry regions of the world that were defined based on the climatological distributions of total and extreme precipitation (Donat et al 2016b, Bador et al 2018, Lehtonen and Jylhä 2019. There is, however, no standard definition for 'wet' and 'dry', and in particular dryness is often considered in a water availability sense as the difference of water supply through precipitation and atmospheric water demand through evapotranspiration (Thornthwaite 1948, Budyko 1974.…”
Section: Introductionmentioning
confidence: 99%